Examining the Influence of Educational and Field Training Programs on Employee Competency at PT. Kereta Api Indonesia (Persero) - Rolanda, Berti Dwi; Elpanso, Efan (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
Organizations face intensified competition in the era of globalization, making effective Human Resources (HR) management crucial for success. This study investigates the impact of education and field training on employee competency at PT. Kereta Api Indonesia (Persero) Divre III Palembang, an enterprise aiming to enhance its railway services. The problem identified is the discrepancy between educational qualifications and practical competencies, exacerbated by insufficient training resources. This research aims to examine how education and field training influence employee competency and to provide recommendations for improving HR practices. Using a quantitative approach, data were collected from 122 employees through questionnaires and observations, supplemented by a literature review. Hypotheses were tested using multiple regression analysis and statistical tests. The findings reveal that education significantly and positively affects competency, which means that higher education levels necessarily equate to higher competency. Then, field training also significantly improves competency, highlighting its effectiveness in developing practical skills. The study also found that both education and field training, when considered together, significantly impact employee competency. Based on these findings, it is recommended that PT. Kereta Api Indonesia (Persero) should consider further evaluating job assignments, differentiating the training materials to meet the competency needs of each position better, and strengthening training programs that focus on developing critical thinking and independent problem-solving skills.